Peritoneal dialysis in the time of coronavirus disease 2019 - Alfano, Gaetano (Clin Kidney J, 2020)
In the current setting of global containment, peritoneal dialysis (PD) and home haemodialysis are the best modalities of renal replacement therapy (RRT) to reduce the rate of transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Considering the shorter and easier training programme of PD compared to home haemodialysis, PD appears a practical solution for patients with end-stage renal disease to reduce the risk of hospital-acquired infection. PD offers the advantage of minimizing the risk of viral transmission through interpersonal contact that commonly occurs during the haemodialysis session and while travelling from home to the haemodialysis facility using public transport services. To overcome barriers to health care access due to the containment measures for this emerging disease, telemedicine is a useful and reliable tool for delivering health care without exposing patients to the risk of contact. However, novel issues including handling of potentially infected dialysate, caregivers’ infectious risk and adequacy of PD in critically ill patients with acute respiratory distress syndrome remain to be clarified. In conclusion, PD should be preferred to the other modalities of RRT during the coronavirus disease 2019 (COVID-19) outbreak because it can be a solution to cope with the increased number of infected patients worldwide.